Postpartum surveillance of bacteriuria in term vaginal deliveries. - Orrett, F. A. (National Medical Association, 1998)
This study examined the prevalence of bacteriuria in early postpartum period after term vaginal delivery in Trinidad, West Indies. Asymptomatic bacteriuria occurred in 58 (34.5%) of 168 patients tested. The prevalence of bacteriuria was significantly higher in non-catheterized patients than in catheterized patients and occurred more commonly in patients who were 20 to 29 years old and who were primigravida rather than multigravida. Forty-four patients had a history of urinary tract infection; 18 (40.9%) of these patients had positive urine cultures. Although 10 patients had a vaginal discharge in the late third trimester, none presented with postpartum bacteriuria. Because of the high prevalence of postpartum bacteriuria and the potential to progress to pyelonephritis and chronic renal disease, quantitative urine cultures for all postnatal patients and curative treatment for all positive cultures are recommend.